THE EXTRAORDINARY LIFE OF AMELIA EARHART - Kanani, Sheila, Dr.; Corcoran, Rachel (London : Puffin Books, 2020)
Amelia Earhart broke flying records, wrote best-selling books, launched a fashion label and fought for the rights of female pilots everywhere. Her disappearance, in the midst of her attempt to circumnavigate the globe, is one of history's greatest unsolved mysteries, and today she is remembered as not only the first female pilot to cross the Atlantic Ocean, but for being a bold, brace and adventurous woman who fought tirelessly for what she believed.
Includes bibliographical references and index.
7-12 ages
Keywords: Earhart, Amelia, 1897-1937 -- Juvenile literature; Women air pilots -- United States -- Biography -- Juvenile literature; Air pilots -- United States -- Biography -- Juvenile literature